DEVELOPMENT OF A BIOTECHNOLOGY E-MODULE INTEGRATED WITH THE PROBLEM-BASED LEARNING MODEL INCORPORATING SOCIOSCIENTIFIC ISSUES TO TRAIN STUDENTS’ CRITICAL THINKING SKILLS - Janand, Handy Ichsa; Adila, Agista Sintia Dewi; Dewantari, Nuryunita (Universitas Tanjungpura, 2026)
Critical thinking skills (CTS) are essential competencies in science education for preparing students to respond to complex socioscientific challenges in the 21st century. Nevertheless, empirical evidence and classroom practices indicate that Indonesian students’ CTS remain at a low level, particularly in biotechnology learning, which often requires higher-order reasoning. This condition is exacerbated by the dominant use of textbook-centered instruction and the limited availability of digital teaching materials that systematically integrate real-world socioscientific issues (SSI). Therefore, the development of innovative, context-based instructional materials is urgently needed. This study aimed to examine the validity, practicality, and effectiveness of a science e-module integrating the Problem Based Learning (PBL) model and SSI to enhance students’ CTS in biotechnology. A Research and Development approach using the ADDIE model was employed, involving 32 ninth-grade students at a Public Junior High School 11 Magelang. Data were collected through expert validation sheets, student response questionnaires, and CTS pretest–posttest instruments. The results showed that the e-module was valid (Aiken’s V = 0.92), practical (81%), and effective in improving students’ CTS, as indicated by a significant Wilcoxon Signed-Rank Test result (p = 0.000) with a moderate N-Gain of 0.47. These findings suggest that integrating PBL and SSI in a digital e-module effectively supports the development of students’ critical thinking skills in science learning.